Failure response of expanded metal meshes subject to transversal impact - Martínez, Gabriela; Casanova, Euro; Graciano, Carlos (Latin American Journal of Solids and Structures, 2023)
This paper aims at investigating the failure response of expanded metal meshes subject to transversal impact. Firstly, the study is performed through explicit nonlinear finite element analysis, in which a numerical model is developed to determine the impact performance and failure mode of expanded metal meshes. Thereafter, the effect of expanded metal cell geometries, impact mass and velocity on the structural response of the meshes is analyzed. Then the perforation resistance of the impacted meshes is assessed and analyzed by means of vulnerability curves for various expanded metal geometries subject to transversal impact. The extent of damage in the meshes is also evaluated, and the maximum displacements achieved in each impact scenario is quantified. At the end, it is demonstrated that the perforation performance of the meshes depends on the expanded metal cell dimensions expressed as a combination of the strand cross-section and major axis length. Finally, the results also show the feasibility of using expanded metal meshes to protect structures impacted by flying debris.